Alimentos nutritivos de mi región - Vásquez Quiroz de Buchelli, Bertha Elizabeth (2019)
The present session has been designed taking into account the pedagogical and didactic processes of the area of science and environment, in the students of the third grade of primary school._x000D_ The issue of healthy and nutritious food is essential for the development of our children, as it is well known that malnutrition and anemia are immersed in our child population, so we have to generate change in attitudes and lifestyles through our products. region and country._x000D_ Good nutrition is key in the physical and intellectual development of the children that will be the future of our Country, for this reason the importance of working on this issue and creating an awareness, a positive change in their lives through a healthy lifestyle.